Co-Producing Public Governance: The Role of Non-Governmental Actors in Kampung Lali Gadget Sidoarjo, East Java, Indonesia - Royan Khusnul Arief; Teguh Priyo Sadono; Rachmawati Novaria (Kirana Publisher (KNPub), 2026)
This study explores the practice of public governance through the co-production model initiated by non-governmental actors in Kampung Lali Gadget (KLG), Sidoarjo, East, Indonesia. Rooted in the increasing concerns over children's gadget addiction and the erosion of local cultural literacy, this research employs a qualitative-descriptive approach to examine how community-driven initiatives can serve as alternative forms of public service delivery. Data were collected through in-depth interviews, participatory observations, and document analysis involving community leaders, volunteers, parents, and local institutions. Findings indicate that KLG represents a form of citizen-initiated co-production, in which local youth and civil society actively engage in designing, implementing, and evaluating community-based educational services. The integration of traditional games, cultural learning, and environmental interaction has proven effective in reshaping children's behavior, enhancing community cohesion, and stimulating local economic activities. KLG's governance structure demonstrates adaptive capabilities, with layered evaluation mechanisms aligned with network governance principles. The study concludes that co-production by non-governmental actors, when grounded in local wisdom and social innovation, can provide sustainable public services that are educationally transformative, socially inclusive, and economically empowering. It also contributes to expanding the literature on co-production in community-based education and offers a replicable model for other regions facing similar sociocultural challenges.